2022
DOI: 10.1002/dad2.12251
|View full text |Cite
|
Sign up to set email alerts
|

Plasma microRNA vary in association with the progression of Alzheimer's disease

Abstract: Introduction Early intervention in Alzheimer's disease (AD) requires the development of an easily administered test that is able to identify those at risk. Focusing on microRNA robustly detected in plasma and standardizing the analysis strategy, we sought to identify disease‐stage specific biomarkers. Methods Using TaqMan microfluidics arrays and a statistical consensus approach, we assessed plasma levels of 185 neurodegeneration‐related microRNA, in cohorts of cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 63 publications
(108 reference statements)
0
14
0
Order By: Relevance
“…Even with different analysis approaches, there is one common serum miRNA (miR-143–3p), and it was shown that inhibition of this miRNA might promote neuronal survival according to an AD cell model . In another study, a significant association among miR-27a-3p, miR-27b-3p, and miR-324–5p and Aβ loads among cognitively normal Aβ-positive, MCI, and AD participants was identified . No overlapping miRNAs were found, possibly due to different populations, disease stages, and study design.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Even with different analysis approaches, there is one common serum miRNA (miR-143–3p), and it was shown that inhibition of this miRNA might promote neuronal survival according to an AD cell model . In another study, a significant association among miR-27a-3p, miR-27b-3p, and miR-324–5p and Aβ loads among cognitively normal Aβ-positive, MCI, and AD participants was identified . No overlapping miRNAs were found, possibly due to different populations, disease stages, and study design.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been suggested that plasma miRNA levels change before the onset of symptoms and vary dynamically with disease progression. 31 There has been increasing evidence suggesting that the PI3K/ AKT pathway plays a key role in the pathophysiology of AD. 56,59,63 This pathway governs a multitude of biological processes, including cell proliferation, motility, growth, survival, and metabolic functions, while also acting to inhibit numerous neurotoxic mechanisms.…”
Section: ■ Discussionmentioning
confidence: 99%
See 3 more Smart Citations